2011
DOI: 10.1177/1088767911417803
|View full text |Cite
|
Sign up to set email alerts
|

Intimate Versus Nonintimate Partner Murder

Abstract: To explore whether homicide of intimate partners is distinct from homicide of nonintimates, we compared sociodemographic, legal, family, clinical, and situational characteristics of men who murdered an intimate partner (n = 71) to those of men who murdered a nonintimate (n = 363). Bivariate findings suggest that intimate murder offenders are more socially bonded and conforming regarding employment and relationship patterns and use fatal violence to meet emotional rather than instrumental needs compared to noni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
34
3
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 41 publications
7
34
3
2
Order By: Relevance
“…Thomas, Dichter, and Matejkowski (2011) observed differences between intimate partner murder offenders and non-intimate partner murder offenders. Specifically, intimate partner murder offenders were more socially integrated and used fatal violence to satisfy emotional aspects in contrast to non-intimate partner murderers whose violence seemed to be rather instrumental.…”
Section: Batterers In Prisonmentioning
confidence: 84%
See 1 more Smart Citation
“…Thomas, Dichter, and Matejkowski (2011) observed differences between intimate partner murder offenders and non-intimate partner murder offenders. Specifically, intimate partner murder offenders were more socially integrated and used fatal violence to satisfy emotional aspects in contrast to non-intimate partner murderers whose violence seemed to be rather instrumental.…”
Section: Batterers In Prisonmentioning
confidence: 84%
“…Specifically, intimate partner murder offenders were more socially integrated and used fatal violence to satisfy emotional aspects in contrast to non-intimate partner murderers whose violence seemed to be rather instrumental. Furthermore, they seemed to differ in marital status, history of severe mental illness, and motives (Thomas et al, 2011). Likewise, Swogger, Walsh, and Kosson (2007) compared antisocial batterers with other antisocial criminals that did not perpetrate IPV against women and found a different profile in affective experience, impulsivity, and irresponsibility.…”
Section: Batterers In Prisonmentioning
confidence: 99%
“…(Dobash, Dobash, Cavanagh, & Lewis, 2004, p. 599). A comparison of intimate partner murders (IPM) with other murders showed that the perpetrators of IPM are more socially bonded (married and employed), more likely to have mental health problems, and more likely to use violence to meet emotional rather than instrumental needs (Thomas, Dichter, & Matejkowski, 2011). Recently, Juodis, Starzomski, Porter, and Woodworth (2014a) compared the correctional files of 37 males convicted of domestic homicide (DH) (including homicides of children, women's new partners, family members, friends, and third-party interveners) with those of 78 non-domestic homicide (NDH) perpetrators (involving the killing of 34 women, nine children, and 29 men).…”
Section: Article In Pressmentioning
confidence: 99%
“…Some research indicates that this crime is more common among antisocial or pathological PVM (basically, those with borderline features) (Dixon, Hamilton-Giachritsis, & Browne, 2008) and that socially disadvantaged groups are overrepresented among male IPH offenders; for instance, "permanently unemployed male alcoholics with a long history of violence" (Kivivuori & Lehti, 2012, p. 73). Others, however, describe socially bonded and non-pathological offenders among these IPH (Dobash & Dobash, 2011;Dobash et al, 2009;Dobash et al, 2004;Dobash, Dobash, Cavanagh, & MedinaAriza, 2007;Dutton & Kerry, 1999;Thomas et al, 2011). Some authors who have examined differences between IPH and non-IPH offenders argue that little has been done about male perpetrators (Juodis et al, 2014a), while others note that most research has focused on victims and incidents (Thomas et al, 2011).…”
Section: Article In Pressmentioning
confidence: 99%
See 1 more Smart Citation